Proceedings of the International Conference on Maritime and Archipelago (ICoMA 2018) 2019
DOI: 10.2991/icoma-18.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Mangrove in Kelapan Island, South Bangka Regency

Abstract: Mangrove forests are an important coastal renewable resources which were found in the brackish water, estuary, lagoon, and tropical island. These forest provide important ecosystem goods, create the new island in the coastal area and biofilter's supporting as a place to live, to spawn, to feed and coastal food web. One of the area in South Bangka Regency, Bangka Belitung Province, which found high biodiversity species and density mangroves is a Kelapan Island. A little Information about mangrove spatial distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…These unreported species include Avicennia alba, Bruguiera sexangula, Ceriops tagal, Excoecaria agallocha, Lumnitzera littorea, and Pandanus tectorius. Moreover, our findings revealed that other species such as Acanthus ilicifolius, Acrostichum speciosum, Aegiceras corniculatum, Bruguiera cylindrica, Bruguiera parviflora, Bruguiera sexangula, Ceriops decandra, Nypa fruticans, and Scyphiphora hydrophyllacea had also not been encountered or reported in previous studies in the Bangka Selatan Regency [45,[61][62][63]. Likewise, studies in the Bangka Tengah Regency [24,30,31,42,43,64] had not reported species such as Aegiceras corniculatum, Bruguiera cylindrica, Ceriops decandra, and Scyphiphora hydrophyllacea.…”
Section: Mangrove Species Composition and Distribution On Bangka Islandsupporting
confidence: 56%
“…These unreported species include Avicennia alba, Bruguiera sexangula, Ceriops tagal, Excoecaria agallocha, Lumnitzera littorea, and Pandanus tectorius. Moreover, our findings revealed that other species such as Acanthus ilicifolius, Acrostichum speciosum, Aegiceras corniculatum, Bruguiera cylindrica, Bruguiera parviflora, Bruguiera sexangula, Ceriops decandra, Nypa fruticans, and Scyphiphora hydrophyllacea had also not been encountered or reported in previous studies in the Bangka Selatan Regency [45,[61][62][63]. Likewise, studies in the Bangka Tengah Regency [24,30,31,42,43,64] had not reported species such as Aegiceras corniculatum, Bruguiera cylindrica, Ceriops decandra, and Scyphiphora hydrophyllacea.…”
Section: Mangrove Species Composition and Distribution On Bangka Islandsupporting
confidence: 56%
“…A similarity in shape and distribution was illustrated in Figure 3a,b between mangrove populations derived from NDVI indices and the referenced mangrove map. Previous studies implemented the mangrove classifications in the world using the NDVI, obtained from high-resolution Quick Bird multispectral satellite imagery with a 2.4 m spatial resolution and a ground truth measurement [10,45]. These studies also observed that the mangrove species obtained from the NDVI value was recorded as above 0.3.…”
Section: Potential Of the Ndvi In Analyzing Mangrove Conditionmentioning
confidence: 91%
“…The increasing values from 0 to +1 depict the presence of vegetation, and near +1 indicates the denser vegetation covered in the area. If the value decreases beyond 0 to −1, it represents the present of bare land, water bodies, ice, snow and manmade features [10,45]. In this study, the Digital Number (DN) value of the NDVI images are categorized from low density to high density as per Table 1 [46,47].…”
Section: Normalized Difference Vegetation Indexmentioning
confidence: 99%